An Overview of Asian Rhinoplasty. (February 2016) - Li, Dong; An, Yang; Yang, Xin
Abstract : Abstract: East Asian rhinoplasty is an expanding topic in the field of rhinoplasty. Although the main principles of various rhinoplasty techniques apply equally to the East Asian nose, East Asian rhinoplasty is unique owing to its different anatomy and ethnicity. In recent years, there have been some noteworthy developments in East Asian rhinoplasty. Traditional techniques using alloplastic implants with endonasal approach are changing due to the advent of new beauty concept, introduction of new techniques, and development of newly improved materials expended polytetrafluoroethylene as an alloplastic material has gained popularity in Asian augmentation rhinoplasty. Soft expended polytetrafluoroethylene sheets as augmentation material provide promise in the future. In this review, we will highlight some of the recent advances of Asian rhinoplasty with emphasis on dorsal augmentation, advances in implant material, and tip surgery using autologous cartilage.